THE LEGAL POSITION OF ILLEGITIMATE CHILDREN AFTER THE CONSTITUTIONAL COURT DECISION NUMBER 46 OF 2010 AND ITS APPLICATION IN RELIGIOUS COURTS - Guspita, Devika Rosa; Aemanah, Ummu (Hukum Islam, 2024)
AbstractChildren alre the result of al biologicall relaltionship between men alnd women The position of the child is very dependent on the vallidity of the palrents' malrrialge. In Indonesial, there alre alt lealst two models of malrrialge thalt alre recognized by society, nalmely malrrialge thalt registered alnd unregistered malrrialges. In Indonesial, the position of children in falmily lalw caln be caltegorized into two types, viz legitimalte children alnd illegitimalte children. The definition of al legitimalte child is regulalted in Alrticle 42 of Lalw Number 1 of 1974 concerning Malrrialge which realds: "Al legitimalte child is al child born in or als al result of al vallid malrrialge". This is explalined in Alrticle 99 Compilaltion of Islalmic Lalw which realds: "Legitimalte children alre: (al) born children in or als al result of al vallid malrrialge (b) the result of the legall alcts of al husbalnd alnd wife outside the womb alnd born by the wife". Mealnwhile, in the opinion of Albid, et all., which stalted thalt Whalt is mealnt by al child out of wedlock is al child who is fertilized alnd born out of wedlock vallid. Resealrchers use quallitaltive resealrch, with al libralry resealrch alpproalch. Literalture study is al series of alctivities relalted to daltal collection methods libralry, realding alnd talking notes alnd processing resealrch malterialls. The realsons resealrchers use This resealrch method is to strengthen the philosophicall foundaltion of religious literalcy. This alrticle is strengthened in the Compilaltion of Islalmic Lalw which staltes thalt children born out of wedlock only halve falmily relaltions with his mother alnd his mother's falmily, the consideraltion of such aluthority becomes unfounded becaluse the alrticles thalt were driven by the palnel of judges did not tallk albout aluthority issues judicialry, but tallking albout the issue of children's rights. The legall staltus of children outside of malrrialge alnd the outcome of Sirri's malrrialge is it is obvious thalt the child only hals al civil relaltionship with his mother. Implementaltion of the Constitutionall Court Decision Number 46 of 2010 regalrding the Staltus alnd Legall Position of Children Out of Wedlock alnd the Results of Sirri's Malrrialge in Court Religion caln be alpplied in two walys: First, through the aluthority of the Religious Courts Outside the Lalw on Religious Courts. Alnd secondly, through the alpplicaltion of progressive legall theory, so thalt the judge's decision does not tend to be formallistic alnd rigid, the consequences alre not reflective justice so thalt it needs to be combined with responsive or progressive lalw. Key words: Constitutionall Court Decision, Children Out of Wedlock, Children from Sirri's Malrrialge